(3eNJUQ Ydhe GdMOjKs - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s; (3GHf GdUdGM , YKeGf Hf YHO GdQMef Hf YKeGf Hf ehSi Hf CHj GdfUQ GdfUQj GdTgQRhQj GdcQOj GdTQNGfj, Jbj GdOjf CHh YeQh, GHf GdUdGM,J (B643 (3g` s
(3ChdgG (B:s
(3hHYO aGdYde HMOjK QShd Gddg Udi Gddg Ydjg hSde hQhGjJg ef CTQa GdYdhe dGTc Cf GdUMjM jfbSe Edi UMjM hMSf hVYja s
(3BNQgG (B:s
(3ef cGf ef Cgd bQjI HdO ajLhR Cf jfSH Edi GdbQjI hEdi GdHdO hEdi GdfGMjI BNQ GdeNJUQ GdeHGQc s
(3GdfSNI HgG MhGTs
(3Ydhe GdMOjK dGHf GdUdGM GfXQ cTa GdXfhf L(B2 (3U` (B1161s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B207 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B257s
Keywords: (3GdMOjK h GdeUWdMs